2018
DOI: 10.3233/cbm-181628
|View full text |Cite
|
Sign up to set email alerts
|

EIF3B correlates with advanced disease stages and poor prognosis, and it promotes proliferation and inhibits apoptosis in non-small cell lung cancer

Abstract: EIF3B overexpression correlates with advanced disease conditions and poor prognosis, and it promotes cells proliferation while inhibits apoptosis in NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 21 publications
0
39
0
Order By: Relevance
“…All IHC procedures were performed as described in a previous study [13]. Finally, the expression of katanin P60 in tissue specimen was assessed by IHC score, which was obtained using a semi-quantitative scoring method as previously described [14]. The total IHC score was ranging from 0 to 12.…”
Section: Ihc Stainingmentioning
confidence: 99%
“…All IHC procedures were performed as described in a previous study [13]. Finally, the expression of katanin P60 in tissue specimen was assessed by IHC score, which was obtained using a semi-quantitative scoring method as previously described [14]. The total IHC score was ranging from 0 to 12.…”
Section: Ihc Stainingmentioning
confidence: 99%
“…Several studies have demonstrated that overexpressed eIF3b could promote the progression of malignant cancers such as glioblastoma cells [14],colon cancer [15], osteosarcoma [16] and lung cancer [17]. In addition, we have revealed the tumor-promoting function of eIF3b in ESCC in previous study [6], however, the underlying molecular mechanism remains elusive.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, high expression of EIF3B was associated with poor relapse-free survival in the subgroups of females, older patients, R0, G2 and stage III. However, Tian et al (11) reported that upregulation of EIF3B was associated with tumor depth, TNM stage and lymph node metastasis in patients with esophageal squamous cell carcinoma. However, the results of the present study indicated that EIF3B was related to histological grade and survival status.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was observed that upregulation of EIF3B was associated with poor overall/relapse-free survival of patients with liver cancer. In addition, patients with high EIF3B expression in clear cell renal cell carcinoma, esophageal squamous cell carcinoma and non-small cell lung cancer had a shorter survival time (6,7,11). In order to further explore the association between EIF3B and clinical characteristics of patients with liver cancer, a subgroup analysis was performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation